Suction blister epidermal grafting for neuropathic ulcer in leprosy - Reeza Edward Yuwantana; Yohanes Widodo Wirohadidjojo (Wolters Kluwer Medknow Publications, 2018)
Leprosy is one of the leading causes of chronic wound cases, especially in endemic countries, where the successfulness of disease elimination has not been followed by reduced rates of leprosy-related disabilities. Chronic nonhealing ulcers are often difficult to treat and have a significant impact on the patient's quality of life as well as an economic burden. Suction blister epidermal grafting (SBEG) was invented as an alternative approach for recalcitrant cases with some advantages above conventional skin grafting techniques. However, availability of sophisticated technologies to harvest grafts is a common problem in most facilities in Indonesia along with prohibitive cost for most patients who are below the poverty line. To overcome such limitations, we implemented a simplified SBEG procedure using daily medical instruments and equipments to provide an affordable service to a neuropathic plantar ulcer patient due to leprosy with satisfying result.